Improving Non-Motorized Transportation Provision in a Socially Inclusive Way—the Case of Cape Town - Vanderschuren, Marianne; Newlands, Alexandra; Wheeldon, Andrew (Frontiers in Sustainable Cities, 2022)
Walking is the most important mode of transport in the ‘Global South’. Depending on the location, the mode accounts for between 33% and 90% of trips. Despite its importance and the notion that walking is available to all, there are vast parts of the population that cannot use the mode, as infrastructure is not conducive. The gender and ability neutral approach to infrastructure provision ignores the needs of up to 75% of inhabitants, leading to isolation and the inability to access services. This paper describes the results of a desktop study that uses various types of literature and secondary data sources to conduct a qualitative assessment of the inclusivity of non-motorized transport and vulnerable population groups (women, children, the elderly, and people with disabilities) in its planning and implementation approach, rather than actual implementations. Cape Town is used as a case study city. Results were verified by local experts. Gender neutral planning and roll out of infrastructure has been slow and there is no evidence at all that women, children, and the elderly are considered in the ‘Global South’ context. Regarding people with disabilities, there has been some progress. Tactile paving and drop curbs are occasionally included. However, due to a lack of training of contractors and personnel that audits implementation projects, the quality of infrastructure for people with disabilities is poor. In the case of Cape Town, the qualitative scores are a mere two credits out of a maximum of 75 credits regarding the non-motorized transport, gender and social inclusion in transportation planning and practice. The authors suspect that scores in many African cities will be even lower. As with many other cities in the ‘Global South’, and more specifically in Africa, Cape Town needs to change its management structure, break down the silos between departments, embrace the input of representatives of vulnerable groups during infrastructure design and implementation and, more importantly, increase the budget for non-motorized transport. There is also a clear need for improved training for contractors and city infrastructure auditors, as implemented infrastructure is often substandard. The study resulted in the development of a hierarchical framework.